1995
DOI: 10.1111/j.1553-2712.1995.tb03602.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Procedures Important to the Training of Emergency Medicine Residents: Who Performs Them in the Emergency Department?

Abstract: Objective: To quantify one aspect of emergency medicine (EM) Results: All 98 EMRPs meeting entry criteria responded to the survey. The medians for the percentage of times index procedures were performed in the E D by an EP were as follows (parentheses following percentages enclose 95% CIS): endotracheal intubation, 97% (95%, 100%); reduction of anterior shoulder dislocation, 93% (88%. 97%); thoracostomy, 63% (50%, 75%); transvenous pacer insertion, 60% (50%, 75%); cricothyrotomy, 50% (50%, 75%); thoracotomy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Gallagher et al recently reported the results of a cross-sectional survey of EM residents, in which they found that EPs in EDs that have active EM residents perform on average 50% of a set of index procedures. 9 Numerous other authors have reported experience in teaching EM procedural skills. 10,11 Some authors have used animal laboratory settings [12][13][14] and procedures on the newly dead in the ED 15,16 as well as computer-based technologies in teaching EM procedural skills.…”
Section: Discussionmentioning
confidence: 99%
“…Gallagher et al recently reported the results of a cross-sectional survey of EM residents, in which they found that EPs in EDs that have active EM residents perform on average 50% of a set of index procedures. 9 Numerous other authors have reported experience in teaching EM procedural skills. 10,11 Some authors have used animal laboratory settings [12][13][14] and procedures on the newly dead in the ED 15,16 as well as computer-based technologies in teaching EM procedural skills.…”
Section: Discussionmentioning
confidence: 99%
“…DJP imported, merged, and organized the data, performed all statistical analyses, prepared all tables, and contributed, by writing or editing, to all sections of the manuscript. dency training in emergency medicine emphasizes airway management, including use of rapid sequence intubation (RSI), defined as intubation after rapid induction and paralysis (1,2). Several previous studies, mostly with small samples, have reported intubation success rates within single institutions, but comprehensive large multicenter studies are lacking (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…This literature and a number of airway courses (e.g., the U.S. based Airway Course® and the Canadian-based Airway Interventions and Management Education Program -AIME®) suggest RSI be considered the default method of intubation unless a contraindication precludes it. In the U.S. and Canada, EP manage the vast majority of patients requiring emergency intubation [1][2][3][4][5][6][7] and, in most of these centres, neuromuscular blocking agents (NMBAs) are used to facilitate intubation as part of a rapid-sequence intubation. 1,[3][4][5][6]8 This practice has raised some concern in the anesthesia community.…”
Section: Conclusion : Le Rôle Des Non-anesthésiologistes Dans L'assismentioning
confidence: 99%